Prosthetic intermediaries in oral implantology: Literature review - Padilla-Avalos, César-Augusto (2021)
Prosthetic intermediaries in oral implantology are attachments that allow connection between the implant and the prosthesis itself. Although this rehabilitation has a high success rate; the selection of the prosthetic abutment represents is important in implant treatment. Currently, there is a great variety of intermediate abutments, corresponding to various techniques and materials. Prosthetic intermediaries can be classified according to the type of connection, their retention to the prosthesis, their axial relationship with the implant body, the manufacturing material and type of manufacture, or whether rehabilitation is single or multiple. This scenario can lead to doubts as to the selection of the ideal implant attachment in each case in order to achieve satisfactory rehabilitation, as well as functional and aesthetic requirements and the preservation of biological principles. Indeed, oral implantology has revolutionized dentistry and will continue to expand the range of possibilities; therefore, it is important to classify the prosthetic options available. The present literature review aims to demonstrate the different alternatives and options available for the intermediate abutments most used in implant prostheses.